Exploring Self-Directed Learning Practices of an Arabic Language Teacher: A Phenomenological Study to Enhance Teaching Quality - Ilmiani, Aulia Mustika; Mubarak, Mahfuz Rizqi; Samdouni, Soukaina (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2023)
The reason for choosing this research stems from the researcher's interest in exploring the practice of an Arabic language teacher who conducts self-study, to improve the quality of learning that he does. The qualitative research method, using a phenomenological approach, was chosen because it was felt that this research method was the most appropriate to further explore information related to independent learning carried out by Arabic language teachers. Data was collected by looking at the whole process of daily activities, in-depth interviews, and observations of independent learning carried out. The subject of this research is an Arabic teacher who was chosen based on the criteria of self-learning represented through daily activities. The results of this study report that there are seven independent learning activities carried out, namely: reading, watching video tutorials, listening to podcasts, taking online courses, conducting experiments, discussing with others, and attending training programs. This research contributes to expanding the study of self-learning, which is important for teachers to do, as a self-effort to improve the quality of Arabic language learning.